Asia-Pacific Consensus Statement on integrated 24-hour activity guidelines for children and adolescents. Issue 10 (8th November 2021) - Loo, Benny Kai Guo; Okely, Anthony David; Pulungan, Aman; Jalaludin, Muhammad Yazid
Abstract : Non-communicable diseases (NCDs) constitute a significant public health challenge and pose a great burden on health and social systems throughout the world. The Asia-Pacific region is in a vulnerable position as the prevalence of NCDs will inevitably increase with rapid socioeconomic transitions; yet it is ill prepared for this public health challenge as Asian children are among the most physically inactive in the world. Aligned with the WHO's global strategy to control NCDs via preventive measures and health promotion policies, representatives from the Asia-Pacific region came together to develop consensus statement on integrated 24-hour activity guidelines for children and adolescents. These guidelines apply to children and adolescents, aged 5–18 years, in the Asia-Pacific region, regardless of gender, cultural background or socioeconomic status. These guidelines aim to provide the latest evidence-based recommendations, taking a holistic approach to lifestyle activities and adopting a practical perspective by framing these activities within a 24-hour period. Eating and dietary elements were incorporated as they closely influence the energy balance of the movement behaviours and vice versa. By investing in the younger generations through advocacy for healthier lifestyles, we aim to reduce the burden of NCDs in the Asia-Pacific region.